GAMBARAN STATUS GIZI PADA LANJUT USIA DI PANTI WREDHA WANA SRAYA DENPASAR - I Gede Yudiana Putra; Ni Putu Eka Febianingsih (Bali Health Published Journal, 2019)
This study aims to determine the description of nutritional status in the elderly at Panti Wredha Wana Sraya Denpasar. The research method used was an observational description with a sample of 29 respondents. Data collection by interview and anthropometric measurement. The collected data was analyzed descriptively and presented in the form of frequency distribution regarding the nutritional status of the elderly. The results of data analysis showed that the majority of respondents were female (79%). Based on the age group, most of the elderly in the Advanced Old / Old (75-90 years) category were 58.6%. As many as 100% of elderly men have a normal abdominal circumference, while in women only 69.6%. The results of the Body Mask Indeks calculation showed that 55.2% of the elderly in the normal weight category. The shortage of weight in the heavy category is 10.3%, and the category of mild weight deficiency is 17.2%. The nutritional status of the elderly at Panti Wredha Wana Sraya Denpasar is mostly in the normal category, but there are still elderly who lack weight in the heavy category. It is expected that there will be continuous and consistent monitoring of elderly nutritional status at Panti Wredha Wana Sraya Denpasar so that the elderly nutritional status can be controlled.